The use of electrodiffusion for removing chlorides from concrete - Alsabry, Abdrahman (Zielona Góra: Uniwersytet Zielonogórski)
The article presents a description of ion migration in a concrete pore liquid caused by an external electric field. The equation of the flow of aggressive chloride ions is formulated on the basis of partial equations of mass balance. It is assumed that electrochemical potential is in classical form, then an attempt is made to determine the average diffusion coefficient using the inverse diffusion Eq.
Keywords: chloride; electrodiffusion; concrete; modelling